Contemporary urban youth culture in China : a multiperspectival cultural studies of internet subcultures - Sun, Jing (Writer on Chinese youth culture) (Emerald Publishing Limited : Informatiom Age Publishing, Inc., 2019)
In Contemporary Urban Youth Culture in China: A Multiperspectival Cultural Studies of Internet Subcultures, Jing Sun explores contemporary Chinese urban youth culture through analyses of three Chinese Internet subcultural artifacts-A Bloody Case of a Steamed Bun, Cao Ni Ma, and Du Fu Is Busy. Using Douglas Kellner's (1995) multiperspectival cultural studies (i.e., critical theory and critical media literacy) as the theoretical framework, and diagnostic critique and semiotics as the analytical method, Sun examines three general themes--resistance, power relations, and consumerism. The power of multiperspectival cultural studies, an interdisciplinary inquiry, lies in its potentials to explore contemporary Chinese urban youth culture from multiple perspectives; explore historical backgrounds and complexity of cultural artifacts to understand contradictions and trajectories of contemporary Chinese urban youth culture; recognize alternative medias as a space for contemporary urban Chinese youth to express frustrations and dissatisfactions, to challenge social inequalities and injustices, and to create dreams and hopes for their future; recognize that the intertexuality among cultural artifacts and subcultures creates possibilities for Chinese urban youth to invent more alternative media cultures that empower them to challenge dominations, perform their identities, and release their imagination for the future; invite Chinese youth to be the change agents for the era but not to be imprisoned by the era; and overcome misunderstanding, misrepresentation, or underrepresentation of contemporary Chinese urban youth cultural texts to promote linguistic and cultural diversity in a multicultural, multilingual, and multiracial world. Sun argues that contemporary urban youth need to obtain critical media literacy to become the change agents in contemporary China. They need to be the medium of cultural exchanges in the multicultural, multilingual, and multiracial world. In order to best assist contemporary Chinese urban youth in expressing their voices, portraying their hopes, and performing their historical responsibilities as change agents, Sun sincerely hopes more research will be done on the contemporary Chinese urban youth culture, especially on its contradictions and trajectories, with the intent to shed light on more richly textured, nuanced, and inspiring insights into the interconnection between contemporary Chinese urban youth and media power in an increasingly multicultural, multilingual, and multiracial world.
Includes index.
Keywords: Internet and youth -- China.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books